Implementasi Pengelolaan Tanaman Terpadu pada Jagung Hibrida (Zea mays L.) - HARYATI, YATI; PERMADI, KARSIDI (Agrotrop : Journal on Agriculture Science, 2016)
Implementation of Integrated Crop Management to Maize Hybrids (Zea mays L.)Hybridof maizes have a higher yield potential than the composite (open pollinated), because the hybrid has the dominant genes that capable to gain high yields. Integrated Crop Management(ICM) is an approach that promotes the cultivation of crop management, land, water, and plant pests in a synergistic and specific. Assessment carried out in paddy fields belonging to farmers, Farmers Group members Jatikersa, Cicurug Village, Majalengka Sub District,Majalengka District the Month June - August (Dry Season II) 2013. Activity assessment test varieties with 2 treatments: (1) hybrid maize varieties P-21 (private) and (2) hybrid maizevarieties Bima-14 (Balitsereal). Each activity was repeated at 16 wetland plots owned by farmers on the same land each 120m2. The data were analyzed using t-test, then made the relationship between the results of the yield components (number of cobs per plant, length of the cob, diameter cob, number of lines per cob, 100 grain weight) andusing analyzed correlation. The purpose of this study to determine variability and agronomic productivity of hybrid maize varieties using corn ICM approach. The resultapproach to the application of Integrated Crop Managementhybrid maize varieties P-21 can be adapted in paddy fields in Majalengka District and diameter of cob is the result of the most influential component of the yield of maize hybrids.
Keywords: Integrated Crop Management; hybrid maize